MI Polsri Iftar Gathering 2025: Strengthening Fellowship and Social Concern among the Academic Community of Information Management - Rahman, M Arief (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2026)
The iftar gathering within the Information Management academic community of Politeknik Negeri Sriwijaya was organized as a community service-based internal engagement activity to strengthen fellowship, interpersonal communication, and social concern. The program aimed to create a reflective and collaborative space for lecturers, staff, and students to build togetherness during Ramadan while reinforcing institutional values. The method consisted of coordination, preparation, implementation, documentation, and evaluation. The activity included opening remarks, informal dialogue, iftar, and social interaction among participants. The results indicate that the program contributed to improving collegial relationships, strengthening a sense of belonging, and encouraging social awareness among the academic community. The activity also provided a model of simple but meaningful institutional engagement that can be replicated in future academic and social programs. The implication of this activity is the need to maintain regular community-based programs as part of character development and organizational culture in higher education.